Exploring Mathematical Creativity in the Crafting of Hex Flange Nuts: Drawing Regular Hexagons - Fuat, Fuat; Senja, Maya; Labh, Ashor (Universitas Muhammadiyah Malang, 2025)
To realize the vision of Indonesia Emas, where digitalization is transforming various fields, it is crucial to develop computational thinking skills through mathematics learning. In this context, Scratch has emerged as an effective learning media relevant to enhancing these skills. This study aims to conduct a literature review on the application of Scratch as a mathematics learning tool to bolster students' computational thinking abilities. The research method employed is a literature study comprising three stages: organizing, synthesizing, and identifying. The findings indicate that using Scratch as a mathematics learning medium significantly influences the development of students' computational thinking skills. This impact is demonstrated by the enhancement of computational thinking abilities facilitated through Scratch as a medium for learning mathematics. The study suggests that further research is essential to explore the use of Scratch in mathematics education, focusing on students' computational thinking abilities to achieve more innovative and optimal outcomes.